Synergy of Green Accounting, Operational Efficiency, and Marketing Effectiveness in Optimizing Corporate Financial Performance - Putri Sari Nuraini; Ana Kadarningsih (International Forum of Researchers and Lecturers, 2025)
The purpose of this study is to examine the effect of green accounting, operational efficiency, and marketing effectiveness on financial performance in mining companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This study uses a quantitative method based on annual financial report data and annual reports for 3 years (2021-2023) from Mining Companies listed on the Indonesia Stock Exchange (IDX). The research sample includes 83 companies with a total of 249 observation data for (3) periods. Data analysis was carried out using Eviews 12 software with the Multiple Regression Analysis method based on panel data with the Common Effect Model (CEM) method. The results of the study show that Green Accounting has a positive and significant effect on financial performance. Conversely, Operational Efficiency does not have a significant effect on financial performance, while Marketing Effectiveness has a positive and significant effect on financial performance.